Impact of corporate social performance on financial performance evidence from Islamic banks, conventional banks and social banks - Mohamed Sultan, Syed Alwi; Wan Ahmad, Wan Marhaini; Ismath Bacha, Obiyathulla; Ramlee, Roslily (International Shari'ah Research Academy for Islamic Finance (ISRA), 2024)
ABSTRACT Purpose — This study aims to assess the impact of banking models on the relationship between corporate social performance (CSP) and corporate financial performance (CFP) in determining a viable model for sustainable banking.